Advertisement Remove all ads

If the point P(x, y) is equidistant from the points A(a + b, b – a) and B(a – b, a + b). Prove that bx = ay. - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Sum

If the point P(x, y) is equidistant from the points A(a + b, b – a) and B(a – b, a + b). Prove that bx = ay.

Advertisement Remove all ads

Solution

P(x, y) is equidistant from the points A(a + b, b – a) and B(a – b, a + b).

∴ AP = BP

∴ `sqrt([x-(a+b)]^2+[y-(b-a)]^2)=sqrt([x-(a-b)]^2+[y-(a+b)]^2`

∴ [x-(a+b)]2+[y-(b-a)]2 = [x-(a-b)]2+[y-(a+b)]2

∴ x2-2x(a+b)+(a+b)2+y2-2y(b-a)+(b-a)2

= x2-2x(a-b)+(a-b)2+y2-2y(a+b)+(a+b)2

∴ -2x(a+b)-2y(b-a)=-2x(a-b)-2y(a+b)

∴ ax+bx+by-ay=ax-bx+ay+by

∴ 2bx=2ay

∴bx=ay ...(proved)

Concept: Distance Formula
  Is there an error in this question or solution?

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×